Hambatan Komunikasi dalam Pembelajaran Matematika - Wahyuni, Eka (Maktabatun: Jurnal Perpustakaan dan Informasi, 2023)
Effective communication in mathematics education is crucial for ensuring deep conceptual understanding and cognitive development in students. However, various communication challenges often arise, hindering the learning process and negatively impacting student outcomes. This study aims to explore the primary challenges in mathematical communication, including language differences, limitations in the use of visual and digital aids, and discrepancies between students' learning styles and teaching methods. Through a qualitative approach involving literature review and case study analysis, this research identifies that language barriers and mathematical terminology, suboptimal use of visual aids, and the mismatch between teaching methods and students' learning styles are significant obstacles in mathematical communication. The findings suggest that these challenges can lead to misunderstandings, a lack of deep conceptual understanding, and a decrease in student motivation and engagement in learning. As a solution, this study recommends strategies such as clearer explanations of terminology, better integration of visual aids, and adapting teaching methods to align with students' learning styles. By adopting an integrated and adaptive approach, it is hoped that communication in mathematics education can be enhanced, thereby supporting better conceptual understanding and more meaningful learning experiences for students